Bridging The Justice Gap: A Critical Analysis Of Judicial Accessibility In Northern Province Of Sri Lanka : Challenges And Comparative Insights - Dasalya, B.L.D. (The Department of Law, Faculty of Arts, University of Jaffna / Surana and Surana International Attorneys India, 2025)
The population of Sri Lanka largely comprises five ethnic communities; Sinhala, Tamil, Muslim, Burgher and Veddha. These groups' livelihoods and settlements are significantly influenced by historical and regional causes. The Northern Province, which is primarily populated by Tamil people, is significant since it is the third largest province by land yet one of the smallest in population. This research article will examine despite its low population density, the province's wide geographical breadth creates particular obstacles for ensuring equal access to justice. This research critically investigates the sufficiency of judicial infrastructure in the Northern Province, focusing on whether the existing courts meet the population’s needs. Further, based on geographical extent, population distribution, and court density, this research paper contends that the number of Courts in the Northern Province is insufficient and leads to delay of justice. To substantiate this claim, a comparative analysis of the Western, Uva, and North Central Provinces is conducted and illustrates regional variations in judicial resources and access to legal services. Additionally, this research explores the geographical position of the Supreme Court and Court of Appeal of Sri Lanka and establishes the argument that these geographical locations have created logistical barriers for the aggrieved parties from the Northern Province. Based on the research, this article will discuss how these circumstances frequently cause justice to be delayed and challenge the right of equal protection under law, access to justice guaranteed by Sri Lankan Constitution. To strengthen this argument, this research paper references international standards of access to justice, evaluating the country's compliance with these standards and identifying areas for reform. On the other hand, this research highlights the merits of the existing courts in the Northern Province. By identifying these challenges, this research emphasises the importance of judicial reforms to overcome regional disparities in access to justice, particularly in neglected areas like the Northern Province. It also emphasises the significance of integrating Sri Lanka's judicial infrastructure with international standards so that all citizens, regardless of geography, can exercise their Fundamental Rights to justice, effectively and fairly.
Keywords: Access to justice; Fundamental rights; Judicial infrastructure; Northern province